The Implications of Labour Productivity and Labour Costs on the South African Economy - Mongale, Itumeleng Pleasure (Journal of Reviews on Global Economics, 2019)
The research has shown that labour productivity growth has been slowing down. This trend is suggesting that the gains in the quality of employment in several regions of the world might be difficult to sustain. Furthermore, the South African workers were found to have the greatest amount of unproductive time and they are said to be having one of the lowest employee productivity stats in the world. The purpose of this study was to investigate the implications of labour productivity and labour costs on the South African economy. The Ordinary Least Square (OLS) based Autoregressive Distributed Lag (ARDL) approach was employed to analyse the quarterly time series data from 1998 to 2018. Since South Africa is faced with several challenges such as high levels of unemployment, higher wage bills and high levels of poverty; this study is envisaged to provide an empirical evidence to policymakers and union leaders alike to begin to recognise more fully the importance of labour productivity and labour costs towards economic growth. The results indicate that labour productivity has a significant positive impact on economic growth however labour costs have a significant negative impact on the economy of South Africa. Policy formulation should focus on policies that can help to improve the quality of the labour force in order to achieve desired economic growth levels that can help to increase the levels of employment and the reduction of poverty. Similarly, both the workers and the labour unions should be cautious not to milk the cash cow until it dies.